(untitled) (Medical Forum Monthly, 2024)
Objective: To compare ischemic and hemorrhagic types of stroke in tertiary care hospital. Study Design: Comparative study Place and Duration of Study: This study was conducted at the Medical Department of PMC Hospital Nawabshah from August 2018 to January 2019. Materials and Methods: This study included total 50 patients. All patients were admitted from Medical OPD and emergency department of PMCH Nawabshah. All the patients with clinical features of stroke were admitted. CT Scan was done to diagnose properly and treated accordingly. Results: Out of total 50 patients, 32 (64%) were male and 18 (36%) were female. Age ranged from 31 to 90 years in males and females. Majority of patients presented from 61-70 years that were 19 (38%) of all. Ischemic stroke was common. It was 36 (72%) whereas hemorrhagic was in 14 (28%). Conclusion: The incidence of ischemic stroke is common in accordance with age, sex and etiology as compared to hemorrhagic. Age presentation is common from 60 to 70 years.